Respostas
respondido por:
15
Boa tarde..
chamando esses numeros de x e y, temos;
x + y = 37
x - y = 9
soma as duas equações..
2x = 46
x = 46 / 2
x = 23
x + y = 37
23 + y = 37
y = 37 - 23
y = 14
os números são; 23 e 14
chamando esses numeros de x e y, temos;
x + y = 37
x - y = 9
soma as duas equações..
2x = 46
x = 46 / 2
x = 23
x + y = 37
23 + y = 37
y = 37 - 23
y = 14
os números são; 23 e 14
respondido por:
1
A + B = 37
A - B = 9
Temos então que A= 9+B
Substituindo....
(9+B)+B=37
2B+9=37
2B=28
B=14
Logo,
A+14=37
A=23
A - B = 9
Temos então que A= 9+B
Substituindo....
(9+B)+B=37
2B+9=37
2B=28
B=14
Logo,
A+14=37
A=23
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás